CONSTRUCTION OF DIOPHANTINE QUADRUPLES WITH PROPERTY D(A PERFECT SQUARE) (International Journal of Engineering Sciences & Management Research, 2015)
This paper concerns with the study of construction of Diophantine quadruples such that the product of any twoelements of the set added by a perfect square is a perfect square.